BMI status relative to international and national growth references among Pakistani school-age girls - Rizwan Qaisar (BMC, 2021)
Abstract Background A sizable proportion of school-going children from developing countries has abnormal growth parameters, often not standardized with international reference values. We aimed to assess the prevalence of underweight, overweight, and obesity in the schoolgirls of Punjab according to international and local references. Methods In this population-based cross-sectional study, 10,050 school-going girls aged 8–16 years from 12 districts of northern, central, and southern Punjab were recruited. Estimates of normal weight, underweight, overweight and obesity were calculated in the girls according to three international BMI references including centers for disease control (CDC) 2000, the international obesity task force (IOTF) 2012 and world health organisation (WHO) 2007 in addition to a local reference for the population under study. We used Cohen’s kappa statistics to analyse the agreement of our data with reference values. Results There was marked overestimation of underweight (23.9%, 14.5%, 15.2% and 4.37%), slight underestimation of overweight (5.3%, 7.3%, 7.9% and 8.97%) and moderate underestimation of obesity (1.9%, 1.5%, 2.2% and 5.67%) according to CDC, IOTF, WHO and local reference, respectively. When the weight status of the study cohort was compared with the local data, we found comparable results in all four weight categories. Conclusion We recommend population-wide further studies to estimate the prevalence of weight status in school-age girls for devising appropriate references and for planning strategies for public health policy and management.